Cultural Sensitivity of Sputum Bacteria Involved in Chronic Lung Disease and Type of Bacteria Involved in Chronic Lung Disease Sputum - Zahra Imdad, Tehmina Maqbool, Abdul Rehman, Iram Naz, Sundas Ikram, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the type of bacterium involved in sputum of patients with chronic lung disease and to determine the culture sensitivity of bacterium involved in sputum of chronic lung disease patients Methodology: This Cross-sectional study, at Deptt of Pediatric Medicine, The Children’s Hospital, Lahore during 2020 to 2021. Total 160 children meeting the criteria of inclusion were the part of this trial. Then the children were given a petri dish to spit in and the samples were submitted to the medical lab to be analysed for bacteria. Penicillin, Ampicillin, Amoxicillin-clavulanic acid, Erythromycin, Tetracycline, Ciprofloxacin, Cefuroxime, Ceftazidime, Cefepime, Piperacillin-tazobactam, Amikacin, Gentamycin, and Vancomycin were tested on all cultured bacteria after they were identified. Results: we recorded 8.60±2.54 years mean age. The most frequent isolated organism was H-influenza (43.1%) followed by H-Parainfluenza (36.9%) and S. Pneumonia (20%). Sensitivity of Ciprofloxacin, Cefuroxime, Amikacin, Gentamycin, Piperacillin / Tazobactam, Ceftazidime, Cefepime and Vancomycin was significantly higher for H parainfluenza as compared to other isolated bacterium. Conclusion: Results of this study showed that among children with chronic lung disease the most frequency isolated bacterium was H-influenza (43.1%) followed by H-Parainfluenza (36.9%) and S. Pneumonia (20%). Antibiotic sensitivity was significantly higher for H-parainfluenza as compared to other isolated bacteria. Keywords: Bacterium, Sputum, Chronic, Lung disease, Culture, Sensitivity